Trilingual education development in universities of Kazakhstan - M. Z. H. TUSSUPBEKOVA; M. A. IDRISSOVA; B. G. SMAGULOVA; Z. H. K. NURMANOVA; K. K. KULANOVA (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: This paper explores the rise of trilingual education in Kazakhstan and the results of the country’s language policy on the classroom experience. Trinity of Languages is a state-sponsored initiative that offers a promising opportunity for young Kazakhs to thrive in today’s competitive global marketplace. This paper emphasises the need for English learning in the Republic of Kazakhstan, despite the significance of Kazakh and Russian.Method: To gauge students’ interest in learning three languages, we analyse data from focus groups.Findings: The survey findings lend substantial empirical support to the author’s claims about the importance of implementing trilingual education in the academic sphere. Kazakhstan is currently implementing the teaching of three languages in schools. The research is grounded in the trilingual education model that draws on language’s expressive, unifying, and integrative powers.Implications/Novel contribution: A true picture of Kazakhstan’s trilingual education landscape has emerged from this study. Students will use these findings to introduce contemporary methods of learning languages that focus on articulating and unifying language functions and on better understanding the paradigm of trilingual learning.